Answer:
x-intercepts: (-1, 0) and (2, 0)
x-intercept: (-3, 0)
Explanation:
Given quadratic function:
![f(x)=-4x^2+4x+8](https://img.qammunity.org/2023/formulas/mathematics/college/z1dj8wnbqlr49qkm7ema22ly0r969rp67q.png)
The x-intercepts of a quadratic function are the points at which the curve crosses the x-axis ⇒ when y = 0
Therefore, to find the x-intercepts of the given function, set the function to zero:
![\implies -4x^2+4x+8=0](https://img.qammunity.org/2023/formulas/mathematics/college/981mbcf4e9wmqy3v3423fvdbppp62hppxx.png)
Factor out -4:
![\implies -4(x^2-x-2)=0](https://img.qammunity.org/2023/formulas/mathematics/college/4058tdoolg2gelww227bvu8un9etnqg92m.png)
Divide both sides by -4
![\implies x^2-x-2=0](https://img.qammunity.org/2023/formulas/mathematics/college/6fmgqip0aovqp9k2ssvgaf6veaytj6uhwu.png)
Rewrite the middle term as -2x + x:
![\implies x^2-2x+x-2=0](https://img.qammunity.org/2023/formulas/mathematics/college/v2xuleby4kt5qxszxwmbfhjyd3m88fbl2h.png)
Factor the first two terms and the last two terms separately:
![\implies x(x-2)+1(x-2)=0](https://img.qammunity.org/2023/formulas/mathematics/college/rsqnufhjb78k4wrm5frpahgpvjayq1rr3i.png)
Factor out the common term (x - 2):
![\implies (x+1)(x-2)=0](https://img.qammunity.org/2023/formulas/mathematics/college/p7ky09xf0m2skmvlgp3fm74oyh4r6gr66j.png)
Zero Product Property: If a ⋅ b = 0 then either a = 0 or b = 0 (or both).
Using the Zero Product Property, set each factor equal to zero and solve for x (if possible):
![\begin{aligned}(x+1) & = 0 & \quad \textsf{ or } \quad \quad (x-2) & = 0\\\implies x & = -1 & \implies x & = 2\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/57id3irpi6rm7qyy024yuqj0nqjvzuqp8h.png)
Therefore, the x-intercepts are (-1, 0) and (2, 0).
---------------------------------------------------------------------------------------
Given quadratic equation:
![-9 = x^2 + 6x](https://img.qammunity.org/2023/formulas/mathematics/college/5rwi4aqs7xktrd8dxrec2i64nu4tby02ug.png)
Add 9 to both sides:
![\implies x^2+6x+9=0](https://img.qammunity.org/2023/formulas/mathematics/college/a2aqirwiqrg8782dnmyau0jzp0q3vt8jr0.png)
Rewrite the middle term as 3x + 3x:
![\implies x^2+3x+3x+9](https://img.qammunity.org/2023/formulas/mathematics/college/wcycezmiq6g56sb9giexiejcx6hhkblu58.png)
Factor the first two terms and the last two terms separately:
![\implies x(x+3)+3(x+3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/q5glb30a6gr3qb83v4ayldxpij78rwmfzz.png)
Factor out the common term (x + 3):
![\implies (x+3)(x+3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/506dx1ha0hxlhpwyw42jumb72qv7rw81wg.png)
![\implies (x+3)^2=0](https://img.qammunity.org/2023/formulas/mathematics/college/ohk9iiudp851h1nx94v89e2ncvfhekidld.png)
Square root both sides:
![\implies (x+3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/75bqk0jwkk3208rd05k1ur8o3u3b1uv5ud.png)
Solve for x:
![\implies x=-3](https://img.qammunity.org/2023/formulas/mathematics/college/udaukwtpn2p0fmchhi120tqn27vblqmy6k.png)
Therefore, the x-intercept is (-3, 0).
As the function has a repeated factor (multiplicity of two), the curve will touch the x-axis at (-3, 0) and bounce off.